Assessment of Health Risks from Agricultural Soils Contaminated with Polycyclic Aromatic Hydrocarbons (PAHs) Across Different Land-Use Categories of Bangladesh - Sumaya Sharmin; Qingyue Wang; Md. Rezwanul Islam; Weiqian Wang; Yanyan Wang; Christian Ebere Enyoh; Md. Sohel Rana (Applied Sciences)
Polycyclic aromatic hydrocarbons (PAHs) are a matter of deep concern as they pose significant environmental and health hazards due to their persistence, bioaccumulation, and toxic effects. In soils, PAHs accumulate, contaminating ecosystems, entering food chains, and posing threats to plant and human health. This study conducted a comprehensive assessment of PAH contamination in agricultural soils (particle size < 20 µm) across various land-use categories and depths to determine contamination levels and associated health risks, as such comprehensive studies are very rare in Bangladesh. Soil samples were investigated using gas chromatography–mass spectrometry (GC–MS). The findings revealed that the concentrations of ∑16PAH ranged from 299 to 1928 µg/kg, with the lowest levels observed in research areas and the highest in industrial soils. Concentration trends were as follows: industrial areas > coastal areas > local market areas > rural areas > research areas. Higher concentrations were noted for individual PAHs such as Nap, Phe, BbF, and BkF (313.14 µg/kg ± 62.01 to 546.97 µg/kg ± 146.76), while the lowest concentrations were recorded for BghiP, DBahA, and Ind (1.25 µg/kg ± 1.10 to 5.74 µg/kg ± 3.77). PAH levels were highest in surface soils, following a depth sequence of 0–5 cm > 5–10 cm > 10–15cm. The results also showed that low-, intermediate-, and high-molecular-weight PAHs comprised 46.06–83.18%, 16.47–48.68%, and 0.23–6.51% of total PAHs, respectively. The source of PAHs was identified as integration of pyrogenic petrogenic. Children were found to have higher exposure through ingestion compared to adults, with lower exposure through inhalation and dermal pathways. The total incremental lifetime cancer risk (ILCR) for children ranged from 2.03 × 10−8 to 9.07 × 10−7, and for adults from 1.96 × 10−8 to 8.04 × 10−7. Both groups exhibited no carcinogenic risk, as per the USEPA threshold. These findings underscore the need for ongoing monitoring and management strategies to mitigate PAH contamination in agricultural soils, thus protecting environmental and public health concerns.